Diversity and distribution of seaweeds in Saint Martin Island, Bangladesh - Md Masum Billah; MA Kader; Mahmud, Syed Shoeb; , Abdulla-Al-Asif; Siddiqui, Abdullah Al Mamun (Zenodo, 2018)
This present investigation conducted on diversity and distribution analysis of the sub-littoral seaweed flora collected from January to June, 2007 from north part and south part of the Saint Martin Island, Bangladesh has revealed the presence of 37 seaweed taxa, 11 under Chlorophyceae, 14 under Phaeophyceae and 12 under Rhodophyceae. The distribution, diversity and abundance of seaweed flora fluctuate due to temperature, locations and species composition variations in Saint Martin Island.